MULTIPLIER EFEK PENINGKATAN INVESTASI SEKTOR INDUSTRI PENGOLAHAN DI KAWASAN INDUSTRI TERHADAP KINERJA SEKTOR PENGANGKUTAN/LOGISTIK - Winardi Winardi; Heru Kustanto (Jurnal Manajemen Industri dan Logistik (JMIL), 2018)
The manufacturing industry sector is an economic sector that provides the largest contribution to the national economy so that the performance of the manufacturing industry greatly affects overall economic performance. Industrial sector investment is currently required to be located within industrial estates in order to improve efficiency, organize space, manage the environment and optimize the multiplier effects on other economic sectors. This study aims to analyze the multiplier effects of increased investment in the manufacturing industry sector in industrial estate on the performance of the transport/logistics sector. The analysis model uses the Social Accounting Matrix (SAM) Model, which is an effect multiplier analysis. The results of the research show that the increase in investment in the manufacturing industry sector located in the industrial area provides a multiplier effect on improving the performance of the transportation/logistics sector in the form of increased transportation/logistics sector revenues.